Clinical markers predict the efficacy of several immune checkpoint inhibitors in patients with non-small cell lung cancer in China - Wang, Yuxin; Lu, Jiahui; Wu, Chenxi; Fei, Fei; Chu, Zhuze; Lu, Peihua (Frontiers in Immunology, 2023)
Objectives: Immune checkpoint inhibitors (ICIs) are one of the most significant oncological treatment modalities as a result of the rapid advancement of immunotherapy. Programmed Cell Death-Ligand 1 (PD-L1) and tumor mutational burden (TMB) have emerged as key markers for predicting the efficacy and prognosis of ICIs in non-small cell lung cancer (NSCLC), and the predictive role of tumour-infiltrating lymphocytes (TILs) has also received significant attention.However, the prognosis of some individuals cannot be determined by these indicators; for instance, some patients with low PD-L1 expression also benefit from longer survival. Therefore, the purpose of this research was to investigate the connection between new haematological and pathological markers and clinical outcomes in NSCLC patients receiving ICIs.: Seventy-six patients with stage III-IV NSCLC treated with ICIs were included in this study. We used the Mann-Whitney test, COX regression and Kaplan-Meier analysis to retrospectively analyze peripheral blood indicators and survival prognostic data of 76 patients in order to investigate the relationship between baseline neutrophil-to-lymphocyte ratio (NLR) and the efficacy of ICIs. To investigate the correlation between CXCL13, CXCR5, CD8 and the efficacy of ICIs, we assessed the expression levels of aforementioned indicators in biopsied tissues of 10 non-small cell lung tumors by immunohistochemistry (IHC) and immunofluorescence (IF) and performed statistical analysis.Results: Disease control rate (DCR) was higher in patients with baseline NLR <3.4 (p=0.016) and neutrophil percentage <71% (P=0.015). Baseline NLR (HR=2.364, P=0.003) and neutrophil percentage (HR=2.824, P=0.013) had the greatest influence on patients' survival prognosis, with baseline NLR exhibiting a stronger predictive value (AUC=0.717), according to univariate and multifactorial COX regression analyses of progression-free survival (PFS) and overall survival (OS). In NSCLC tissues, higher expression of CXCL13 was associated with better clinical outcomes (P=0.032) and higher expression of CD8 was associated with prolonged survival (P=0.022).Low baseline NLR in peripheral blood and high expression of CD8 in tissues are associated with longer PFS and may have a potential predictive value for patients with stage III-IV NSCLC using ICIs.